Economics, ethics and politics of groundwater: Evidence from West Bengal, India - Mukherji, Aditi (2007)
This paper deals with three different, yet related issues of groundwater use, viz. economics, ethics and politics. One of the most important ethical dilemmas of global groundwater use is that its positive impact on food security, incomes of the poor and poverty alleviation are relatively under-estimated while the negative externalities are often over-emphasized. The first section of this paper deals with this very ethical dilemma by illustrating how the role of groundwater irrigation in sustaining high agricultural growth rates in West Bengal -- an eastern state of India, has been completely over looked in academic discussions so far. Groundwater irrigation has conferred immense economic benefits in terms of increased access to irrigation, higher cropping intensity and productivity. Informal groundwater based irrigation services markets have played an important role in this regard. The second section, based on primary data collected from 580 respondents in 40 villages in the state, specially focuses on groundwater economics and the impact of groundwater supported private irrigation services markets. The third section of the paper concentrates on groundwater politics. It shows that the dominant discourse in the field of groundwater studies in India has been that of depletion and scarcity so much so that the groundwater policies even in a well-endowed state such as West Bengal has been unduly influenced by this dominant discourse. The result has been that of a paradox: little groundwater regulation where resource conditions are precarious (e.g. Gujarat, Tamil Nadu) and strict regulation where little is needed (e.g. West Bengal).